Feasibility of Restorative Circles for Harm Reparation in Obstetric Conflict - Martínez Suárez, Marta; Iglesias Ortuño, Emilia (Mediaciones Sociales, 2025)
The harm caused during obstetric processes goes beyond the physical sphere of the women who suffer it, as it compromises an emotional process that puts their reproductive health at risk. Rigid protocols, institutional inefficiency, and dehumanization are causes of harm to women during childbirth and the postpartum period. Restorative Justice, implemented through Restorative Circles, could be an ideal alternative through which women gain a voice and protagonism. By sharing their stories, they can foster understanding among the professionals involved and achieve reparation for the harm caused. This study, using a Case Study methodological approach, aims to identify the viability of Restorative Circles for harm reparation through the evaluations of women who have experienced obstetric harm. These women will determine the appropriate composition, professional guidance, and execution of such circles. They will also assess the contribution of this alternative to their reproductive and emotional well-being. Key findings highlight that communication, intimacy, and expressions of respect and remorse are essential during a Restorative Circle, which should be led by social professionals with specific training. Furthermore, it is considered a guarantor of their reproductive well-being, for which they suggest going beyond the goodwill of professionals and involving health institutions through protocols that humanize professional practice.